PENGARUH DAYA TARIK IKLAN, ATRIBUT PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA PRODUK MINUMAN RASA JERUK MEREK FLORIDINA - Laily, Viqrul Nadia Nur; Maduwinarti, Ayun; Pujianto, Agung (Universitas 17 Agustus 1945 Surabaya, 2019)
Every company must have its own strategy in running its business such as beverage producers both in terms of promotions, product attributes, prices and so forth. This study tries to explain the influence of advertise attractiveness, product attributes, and price perceptions on purchasing decisions on Floridina brand orange flavored beverage products.This study uses a quantitative method with survey research using a questionnaire as an instrument. The population in this study were all consumers who had consumed Floridina brand orange flavored drinks. The sample of this study was consumers who had consumed / bought Floridina brand orange flavored drinks and found out about Floridina advertisements on television, totaling 100 people. The data analysis technique used is multiple linear regression analysis.The results of the study show that all independent variables, namely the advertise attractiveness, product attributes, and perceived prices have a positive influence on the dependent variable, namely the purchasing decision. The most influential independent variable on the dependent variable is the advertise attractiveness variable (0.330), followed by the price perception variable (0.237), and then the product attribute variable (0.170). All variables have a significance value of <0.05, which means that all independent variables are significant for the dependent variable or pass the t test and F test. And the coefficient of determination (adjusted R2) obtained is 0.426. This means that 42.6% of purchasing decisions are influenced by variable advertise attractiveness, product attributes, and perceived prices. While the remaining 57.4% is influenced by other variables not examined in this study.Keywords: advertise attractiveness, product attributes, price perception and purchasing decisions